2018
DOI: 10.1088/1741-2552/aac77f
|View full text |Cite
|
Sign up to set email alerts
|

Aligned fibrous PVDF-TrFE scaffolds with Schwann cells support neurite extension and myelination in vitro

Abstract: This study demonstrated PVDF-TrFE scaffolds containing aligned fibers supported SC-neurite extension and myelination. The combination of SCs and PVDF-TrFE scaffolds may be a promising tissue engineering strategy for spinal cord repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 80 publications
0
66
0
Order By: Relevance
“…Electrospun fibers can be modified to specifically promote cell proliferation in the context of wound regeneration, [30,31,34] and piezoelectric materials in particular have a unique capacity for enhancing replication of numerous cell types. [16,54,59,67] For instance, Wang et al demonstrated that modulation of the piezoelectric effect in PVDF-TrFE nanofibers with targeted vibrations can increase the proliferation rate of fibroblasts 1.6 fold. [68] Therefore, these results in conjunction with the adhesion assay show both unaligned and aligned scaffolds are biocompatible and capable of facilitating cell proliferation.…”
Section: Cell Adhesion and Integration With Scaffoldmentioning
confidence: 99%
See 3 more Smart Citations
“…Electrospun fibers can be modified to specifically promote cell proliferation in the context of wound regeneration, [30,31,34] and piezoelectric materials in particular have a unique capacity for enhancing replication of numerous cell types. [16,54,59,67] For instance, Wang et al demonstrated that modulation of the piezoelectric effect in PVDF-TrFE nanofibers with targeted vibrations can increase the proliferation rate of fibroblasts 1.6 fold. [68] Therefore, these results in conjunction with the adhesion assay show both unaligned and aligned scaffolds are biocompatible and capable of facilitating cell proliferation.…”
Section: Cell Adhesion and Integration With Scaffoldmentioning
confidence: 99%
“…It is also possible to subvert this caveat by developing integrated devices, such as 3D electrospun, aligned nerve conduits, that incorporate additional material technology to affect cell phenotypes in feasible clinical applications. [16,41]…”
Section: Cell Adhesion and Integration With Scaffoldmentioning
confidence: 99%
See 2 more Smart Citations
“…Scaffolds were prepared using the electrospinning technique. Random or aligned fibrous PVDF-TrFE scaffolds were fabricated by modifying previous methods as described 45 A horizontal electrospinning setup was used to fabricate the PCL and PLA scaffolds. Solutions (15% w/v) were prepared by weighing the appropriate amount of PCL or PLA pellets and dissolving by stirring in dichloromethane.…”
Section: Fabrication Of Scaffoldsmentioning
confidence: 99%